Future perspectives for mTOR inhibitors in renal cell cancer treatment. (March 2015) - Czarnecka, Anna M; Kornakiewicz, Anna; Lian, Fei; Szczylik, Cezary
ABSTRACT : Everolimus is a mTOR inhibitor that demonstrates antitumor and antiangiogenic activities. In a randomized Phase III trial, patients with metastatic renal cell carcinoma who progressed on sunitinib/sorafenib were treated with everolimus and showed significant improvement in progression-free survival compared with best supportive care. Novel approaches in treatment are expected to ensure less toxic therapies and increase efficacy of everolimus. To provide a new perspective for mTOR inhibitor research and therapy, we discuss renal cell carcinoma cancer stem cells as a potential target for mTOR inhibitors and present new concepts on emerging antiangiogenic therapies. Finally, we point why systems biology approach with reverse molecular engineering may also contribute to the field of drug discovery in renal cell carcinoma.